Role of Communication in Empowering Forum Darim Bersatu (Journal of Namibian Studies : History Politics Culture, 2023)
The existence of groups in society as social capital can grow and develop. Forimber (Forum Darim Bersatu), a community group located in Darim Village, Indramayu Regency. This study aims to analyze the role of Forimber group communication in existing empowerment. Research using descriptive qualitative through case study method. The results showed that group communication in Forimber had a better impact on the development of Kampung Darim, through empowerment activities. Communication within the group also helps to create public relations and harmonious information management. Role of communication doesn't only occur among community members but also by building partnerships with various parties to support community empowerment. It isn't limited to empowering individuals in the community, but the Darim village itself. Community participation in Forimber empowerment hasn't been evenly distributed. Group communication in empowerment influences people's communication behavior, as a social means to generate shared energy and provide convenience in building social relations, and problem-solving. The role of communication needs to be increased to encourage equal participation in society, especially among women. The contribution of this study shows that through group communication with the similarity of symbol meanings, the Forimber fantasy theme also raises collective identity within the group to trigger collective action.